Network and migration in early Renaissance Florence, 1378-1433 : friends of friends in the kingdom of Hungary - Prajda, Katalin (2018)
This book explores the co-development of political, social, economic, and artistic networks of Florentines in the Kingdom of Hungary during the reign of Sigismund of Luxembourg. Analyzing the social network of these politicians, merchants, artisans, royal officers, dignitaries of the Church, and noblemen is the primary objective of this book. The study addresses both descriptively the patterns of connectivity and causally the impacts of this complex network on cultural exchanges of various types, among these migration, commerce, diplomacy, and artistic exchange. In the setting of a case study, this monograph should best be thought of as an attempt to cross the boundaries that divide political, economic, social, and art history so that they simultaneously figure into a single integrated story of Florentine history and development.